PENGETAHUAN DAN SIKAP IBU NIFAS TENTANG TANDA BAHAYA NEONATUS DI PUSKESMAS II KARANGASEM BALI TAHUN 2013 - Agung Indra Suharta (DiscoverSys Inc., 2015)
Neonatal mortality or high risk neonates in Karangasem is still high. The largest amount found in Karangasem District. Pneumonia, hipotermy, neonatal jaundice, neonatal tetanus are some causes ofneonatal mortality. The purpose of this research is to determine knowledge and attitudes of post partum women about danger signs of neonatal period. Cross sectional design is used in descriptive observational research. Number of samples were 43 people, with criteria 0 – 28 days post partum women who visit Puskesmas Karangasem II and post partum women who hospitalized at Puskesmas Karangasem II. This research were done for about 2 months, started from June until July 2013. Based on the results, knowledge of respondents had the most good knowledge, as much as 51,16%, respondents who had enough knowledge were 37,21% and respondents who had less knowledge were 11,63%. Specifically, knowledge of postpartum mother less on neonatal jaundice (69,77%) and neonatal tetanus (37,21%). Where as, attitude of respondents about danger signs of neonatal period which had a negative attitude as much as 41,86% respondents